Metagenomic analysis of the human gut microbiome in Inflammatory Bowel Disease - Penas Steinhardt, Alberto (2020)
Fil: Penas Steinhardt, Alberto. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.